(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2023)
The notion of adversity is inherently negative, yet it can be a positive force for change. Inspired by this and in relation to the recent pandemic which saw the lives of the global community disrupted and challenged, the 6th International Conference on Linguistics, Literature and Culture (ICLLIC 2022) chose “Overcoming Adversity, Embracing Change” as the main conference theme. This article is an overview of selected articles from the conference that address issues in language and culture in the Asian context, emerging from the pandemic and contemporary social factors such as globalisation, diaspora and modernity. They include examination of innovations, adaptations and new practices in language, literature and culture that demonstrates Asian linguistic and literary dynamism and resilience in embracing change in the face of adversity.